2021
DOI: 10.1186/s12951-021-00908-2
|View full text |Cite
|
Sign up to set email alerts
|

The neuroprotective effect of pretreatment with carbon dots from Crinis Carbonisatus (carbonized human hair) against cerebral ischemia reperfusion injury

Abstract: Background Cerebral infarction and cerebral hemorrhage, also known as “stroke”, is one of the leading cause of death. At present, there is no real specific medicine for stroke. Crinis Carbonisatus (named Xue-yu-tan in Chinese), produced from carbonized hair of healthy human, and has been widely applied to relieve pain and treat epilepsy, stroke and other diseases in China for thousands of years. Results In this work, a new species of carbon dots de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…Other studies also reported that the hyperphosphorylation of tau increases during MCAO/R in animal models ( Dong et al, 2014 ; Fujii et al, 2017 ). Tnf was also reported to be significantly upregulated in MCAO/R animal models and OGD/R cell models ( Li et al, 2019 ; Zhang et al, 2021a ; Zhou et al, 2021 ). Moreover, it was reported that miR-181a-5p was highly expressed in serum of ischemic stroke patients, brain tissues of MCAO/R mice, and an oxygen-glucose-deprivation/reoxygenation (OGD/R) N2a cell model ( Ouyang et al, 2012 ; Wu et al, 2017 ; Song et al, 2021 ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Other studies also reported that the hyperphosphorylation of tau increases during MCAO/R in animal models ( Dong et al, 2014 ; Fujii et al, 2017 ). Tnf was also reported to be significantly upregulated in MCAO/R animal models and OGD/R cell models ( Li et al, 2019 ; Zhang et al, 2021a ; Zhou et al, 2021 ). Moreover, it was reported that miR-181a-5p was highly expressed in serum of ischemic stroke patients, brain tissues of MCAO/R mice, and an oxygen-glucose-deprivation/reoxygenation (OGD/R) N2a cell model ( Ouyang et al, 2012 ; Wu et al, 2017 ; Song et al, 2021 ).…”
Section: Resultsmentioning
confidence: 96%
“…Many studies have demonstrated that the inhibition of TNF signaling pathways may have neuroprotective effects against cerebral I/R injury. For example, Zhang et al showed that preconditioning with Carbonisatus significantly decreased the levels of TNF-α and IL-6, reduced ischemic lesion volume, and improved neurological deficits in MCAO/R rats ( Zhang et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…Through preparatory work, our investigation group has demonstrated that CDs are the material basis for the activity of charcoal drugs. We have reported that the carbonisata-derived CDs of charcoal drugs such as Junci Medulla 31 have remarkable anti-haemorrhage effects and CDs derived from Crinis Carbonisatus 32 perform neuroprotective effect on cerebral ischemia and reperfusion injury. In addition, Aurantii fructus immaturus 14 carbonisata-derived carbon dots have anti-hyperuricaemic and anti-gouty arthritis activity, which can diminish serum uric acid by restraining xanthine oxidase activity in hyperuricaemic rats and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, although collagen plays a key role in cell-ECM adhesion, another two components of ECM (namely, fibronectin and integrin) are needed as well, since the establishment of the cell-ECM connections is via the binding of fibronectin to collagen and cell-surface integrin [ 11 ]. With excellent biocompatibility, strong fluorescence properties, and nanoscale size, carbon dots (CDots) as an emerging class of carbon-based nanomaterials have great potential in various biomedical applications, including anti-inflammation [ 32 ], bacteriostasis [ 33 ], bioimaging [ 34 ] and so on [ 35 , 36 ]. A majority of CDots are usually prepared from the organic precursors with carbonyl and amine groups through amidation reaction similar to the formation of peptide bond in protein.…”
Section: Introductionmentioning
confidence: 99%